PROSES PEMBUATAN MINIATUR KAPAL PETI KEMAS DAN PETI KEMAS BERBAHAN FIBER REINFORCED PLASTIC (FRP) DALAM SKALA KECIL - Zulkarnain; Nur Rahmani; Robyansyah (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
In the field of sea transportation, especially the transportation of goods or cargo, there have been changes and improvements, namely with the presence of containers which have become a new system. Now this has a comprehensive impact on the cargo transportation system which is increasing over time. The rapid progress of the container system is aimed at delivering cargo safely, quickly and efficiently from the port of origin to the port of destination to avoid cargo damage as little as possible. The purpose of this research is to increase insight and skills to be able to apply the knowledge learned into products that are beneficial to the world of education in the field of transportation. Miniature ships and containers made of fiberglass are very necessary for the development of the maritime world because they are considered superior in terms of cost, maintenance, construction, and manufacturing processes compared to other materials. The research was conducted through a qualitative method by directly observing the object of research, namely miniature container ships and miniature containers and seeing the manufacturing process and analyzing the aesthetic elements. The results obtained are the stages/processes of making miniature container ships and containers starting from the preparation stage and the implementation stage. The parts of the container ship and container miniature are complementary or have a connection with each other and are made with very good details.